Use of carbon disulfide as attractant for trapping and rodenticide baiting of Bandicota bengalensis (GRAY) (SAARC Journal of Agriculture, 2016)
Management of rodent with rodenticide and trapping is frequently ineffective due to bait or trap shyness and neophobia. A study was conducted in the laboratory of Vertebrate Pest Division, BARI, Gazipur and field to increase the attractiveness of bait or trap to B. bengalensis and enhance the consumption of novel food by using different concentration of carbon disulfide (CS2). Study revealed that addition of CS2 improved bait acceptance of food. Five ppm concentration of CS2, rat consumed significantly greater amount of cereal bait than untreated plain wheat bait. In semi-natural field test, significantly greater number (59%) of rat was trapped in CS2 scented bait than without scented bait (41%). In the field study higher population reduction (85-91%) was achieved with CS2 scented zinc phosphide bait than without scented zinc phosphide bait (50%). That is 80% higher reduction of rodent population was achieved with CS2 treated zinc phosphide bait. From this study we conclude that CS2 can improve the efficiency and consumption of poison bait and can increase trap success.SAARC J. Agri., 14(1): 93-101 (2016)